Connectivity analysis of magnetic mineral veins based on multi-boreholes image - Han, Zengqiang; Wang, Chuanying; Hu, Peiliang (Penerbit Universiti Kebangsaan Malaysia, 2017)
There are a large number of primary structural planes of deep rock ore such as rhyolite, and bedding, which are well preserved and are often the geological interfaces of mineralization. Study on the occurrence of these structural planes is helpful to understand the extension direction of deep veins. Using borehole imaging technology as the means of acquiring information of structural plane, the magnetic angle of the borehole is obtained by using the gyroscope and the magnetic instrument and the structural plane occurrence is modified to obtain the accurate information. According to the depth effect of the deep structural plane, the concept of the feature point pair is proposed. In this paper, the mathematical description method of the structural plane in the space coordinate system is established and the information of the shape and depth of the structure plane is transformed into the 3D point coordinates in the space coordinate system. Based on the feature points, the connectivity analysis method of structural plane is established and the connectivity of the structural planes such as the interface of the vein and rhyolite is analyzed. According to the stratigraphic information in the borehole image, the extension direction of the whole field is determined. The feasibility of the method is verified by the application in a magnetite in Anhui Province, China. The results are in good agreement with the actual drilling results and the error of traditional drilling analysis is corrected. The main conclusions of this paper include: The use of gyroscopes and magnetic instrument can obtain the magnetic effect angle, to modify the structural plane information; and multi borehole structural planes connectivity analysis can provide a reference for the extension of the deep veins.